A method for obtaining the electrochemical active area of ​​graphite

Through scanning electron microscope, the relationship between the characteristic size and crystal plane spacing changes of graphite particles was obtained, and the specific surface area of ​​the electrochemically active graphite particles under different SOC states was calculated, which solved the problem of inaccurate acquisition of graphite electrochemically active area in the prior art, and achieved more accurate measurement of electrochemically active area.

CN115144320BActive Publication Date: 2025-04-01SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210772239.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-30
Publication Date
2025-04-01
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

The method of obtaining the electrochemically active area of ​​graphite in the prior art is inaccurate, and there are defects that are significantly smaller or larger.

Method used

The characteristic size of graphite particles was obtained by scanning electron microscope, and the specific surface area of ​​the graphite particles under different SOC states was calculated based on the relationship between the SOC state of the graphite electrode sheet and the crystal plane spacing of the graphite particles in different SOC states, and finally the electrochemical active area of ​​the graphite sheet was obtained based on the mass of graphite in the graphite sheet.

Benefits of technology

This method is closer to the electrochemically active area of ​​graphite than the BET method, and can accurately characterize the electrochemically active area of ​​graphite electrode sheets under different SOC states, avoiding the existence of errors in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115144320B_ABST
    Figure CN115144320B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery material research and development and testing, and specifically relates to a method for obtaining the electrochemically active area of ​​a graphite pole piece. The method for obtaining the electrochemically active area of ​​a graphite pole piece provided by the present invention obtains the characteristic side length of graphite particles in the graphite pole piece by scanning electron microscopy, and selects a suitable formula according to the SOC state of the graphite pole piece, and substitutes the characteristic side length parameter to obtain the electrochemically active specific surface area of ​​graphite particles under different SOC states; the electrochemically active area of ​​the graphite pole piece is obtained according to the mass of the graphite pole piece. The present invention uses the mass of the graphite pole piece, the graphite crystal structure, and the characteristic size of the graphite particles to calculate the electrochemically active area of ​​the graphite pole piece participating in the electrochemical reaction of lithium insertion and extraction. The electrochemically active area is closer to the actual area participating in the lithium insertion and extraction reaction than the area directly using the pole piece area or the area calculated using the BET method. This method can characterize the effective area of ​​the graphite pole piece under different SOC states.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery material research and development testing, and specifically relates to a method for obtaining the electrochemical active area of ​​graphite. Background Art

[0002] Artificial graphite materials have become the most commercially available negative electrode materials due to their advantages such as good cycle performance and conductivity, low lithium insertion potential and small volume expansion. Graphite has a layered structure, with carbon atoms arranged in hexagons in each layer. Its crystal structure is as follows: Figure 1 As shown. In the process of lithium insertion / extraction, lithium ions are mainly inserted / extracted from the graphite layers. Although artificial graphite has many advantages, the modification of artificial graphite negative electrode materials has never stopped, such as: improving the reversible capacity of the negative electrode, the ion diffusion rate, and its compatibility with the electrolyte, in order to obtain batteries with better performance and higher energy density.

[0003] For the study of the performance of artificial graphite, especially its electrochemical performance, it is necessary to accurately grasp the area of ​​graphite actually participating in the electrochemical reaction. For example, the GITT (Galvanostatic Intermittent Titration Technique) method is generally used in the prior art to calculate the diffusion coefficient of the graphite electrode. When using this method, it is necessary to input the surface area of ​​the graphite actually participating in the electrochemical reaction (participating in the de-lithiation / insertion reaction). Therefore, accurately obtaining the surface area actually participating in the de-lithiation / insertion reaction is crucial for the study of electrochemical performance based on the actual electrochemical reaction area.

[0004] In the prior art, the chemically active area of ​​a graphite electrode is generally obtained by using the electrode area or the BET method. However, since the graphite negative electrode is not a dense structure, after being immersed in the electrolyte, each particle may theoretically be in contact with the electrolyte. Therefore, using the area of ​​the electrode to replace the sum of the surface areas of the graphite particles is obviously too small. The use of the BET method can significantly improve the estimation of the surface area of ​​graphite particles, making the obtained surface area closer to the actual surface area of ​​the graphite particles. However, for calculations related to electrochemical reactions during the process of graphite deintercalation and lithium insertion, such as the calculation of the reaction current density of graphite during the lithium insertion process, the use of the BET method will result in significant errors. This is because the insertion or removal of lithium ions from graphite belongs to intercalation diffusion, so only the cross-section of the graphite is electrochemically active, and the upper and lower surfaces cannot undergo lithium deintercalation reactions. Therefore, the graphite surface area obtained using BET is significantly larger than the actual area where the electrochemical reaction occurs. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art methods for obtaining the electrochemical active area of ​​graphite, such as being inaccurate and being obviously too small or too large, thereby providing a method for obtaining the electrochemical active area of ​​graphite.

[0006] The present invention proposes a method for calculating the electrochemical active area of ​​a graphite negative electrode under different lithium insertion states by using the mass of active material in the graphite negative electrode and the characteristic size of graphite particles. The method is closer to the electrochemical active area of ​​graphite than the lithium insertion area obtained by the BET method.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] The present invention provides a method for obtaining the electrochemical active area of ​​a graphite pole piece, comprising the following steps:

[0009] S1, obtaining characteristic dimensions of graphite particles by scanning electron microscopy, including the average length A and average width B of graphite particles;

[0010] S2, determine the interplanar spacing d between graphite particles and different SOC states 100 , d 002 The changing relationship between

[0011] S3, calculate the electrochemical active specific surface area of ​​graphite particles under different SOC states according to the following formula:

[0012]

[0013] S4, obtaining the electrochemical active area of ​​the graphite electrode according to the mass of graphite in the graphite electrode.

[0014] Typically, but not limiting, the characteristic size can be obtained by marking the relatively complete particle size in the scanning electron microscope image of the graphite particles and then calculating the average value.

[0015] Optionally, step S2 includes:

[0016] S21, the XRD spectrum of the graphite electrode during the charge and discharge process is measured by in-situ XRD, and the interplanar spacing d of the graphite particles is determined according to the diffraction angles corresponding to the 100 crystal plane and the 002 crystal plane. 100 and d 002 ;

[0017] S22, the interplanar spacing d between graphite particles and different SOC states were obtained by fitting multiple functions 100 and d 002 The changing relationship between them.

[0018] Optionally, in step S21, the interplanar spacing is calculated according to the following formula:

[0019] 2dsinθ=λ, where θ is the XRD diffraction angle, λ is the X-ray wavelength, and d is the interplanar spacing.

[0020] Optionally, the diffraction angle corresponding to the crystal plane 100 of the graphite particle is 2θ=43-45°.

[0021] Optionally, the diffraction angle corresponding to the 002 crystal plane of the graphite particle is 2θ=17-23°.

[0022] Optionally, the test parameters of the in-situ XRD are conventional test parameters, specifically 20KV and 40A, and the copper target X-ray wavelength is The scanning range is 10°-80°, and the scanning rate is 2° / min.

[0023] Optionally, the different SOC states and the interplanar spacing d of the graphite particles 100 and d 002 The changing relationship between them is:

[0024]

[0025] Optionally, the electrochemical active area of ​​graphite particles under different SOC states is calculated according to the following formula:

[0026]

[0027]

[0028]

[0029]

[0030] Optionally, in step S4, the calculation method of the electrochemical active area of ​​the graphite electrode is:

[0031] S e =m a *A effective ,

[0032] Among them, m a is the mass of graphite in the graphite electrode.

[0033] The principle and derivation process of the present invention are:

[0034] In lithium-ion batteries, the embedding of lithium ions into the negative electrode includes four processes: diffusion of solvated lithium ions in the electrolyte; desolvation of lithium ions that reach the surface of the graphite negative electrode; passage of desolvated lithium ions through the SEI membrane; and diffusion of lithium ions inside the graphite particles. The diffusion of lithium ions in graphite particles occurs along the interlayers, so only the cross-section of the graphite particles allows lithium ions to be embedded in the graphite. Therefore, accurately expressing the electrochemically active area of ​​the graphite pole piece is crucial to studying the deintercalation reaction of lithium ions in the graphite pole piece.

[0035] The main principle of the present invention is based on the relationship between the graphite particles and the grain and crystal plane spacing in the graphite pole piece, such as Figure 1 , Figure 2 As shown, through theoretical derivation and mathematical calculation, the effective (electrochemically active) specific surface area of ​​graphite particles for lithium intercalation and deintercalation reaction (i.e., surface A×C and B×C, Figure 2 ), and then the electrochemical active area of ​​the graphite electrode is obtained according to the mass of graphite in the graphite electrode. Among them, the electrochemical active specific surface area of ​​the graphite particles is expressed as:

[0036]

[0037] The derivation process of the electrochemically active specific surface area of ​​graphite particles is as follows:

[0038] like Figure 1 As shown in FIG. 1 , when the side length of the graphite particle plane is composed of n graphite rings, the maximum width La of the graphite particle can be expressed as La = d 100 (2n-1). Similarly, if the graphite particle is composed of m layers of graphite rings, then the thickness of the graphite particle Lc = d 002 (m-1).

[0039] Quality of graphite particles: (A (average length), B (average width), and C (average thickness) are the characteristic side lengths of graphite particles, M is the relative atomic mass of carbon, and N A is Avogadro's constant);

[0040] Because graphite is an intercalated lithium, graphite particles can only be intercalated with lithium on the side, and the intercalated lithium area is expressed as: S = 2 (AC + BC);

[0041] Electrochemically active area of ​​graphite particles:

[0042] Due to d 002 and d 100 Compared with Lc and La, it is much smaller, so the above formula can be simplified to: Substituting the values ​​into the equation we get:

[0043] Fitting of the relationship between graphite interplanar spacing and SOC:

[0044] First, the XRD spectrum of the graphite electrode during the charge and discharge process is measured by in-situ XRD. The test parameters of the in-situ XRD are 20KV and 40A, and the wavelength of the copper target X-ray is Scanning range 10°-80°, scanning rate 2° / min. According to the formula 2dsinθ=λ (where θ is the XRD diffraction angle and λ is the wavelength of the X-ray (Cu target )) According to the change of XRD diffraction angle θ corresponding to 002 crystal plane and 100 crystal plane, the change trend of the corresponding interplanar spacing is calculated. According to the change trend of interplanar spacing of graphite particles, the graphite particles d 002 and d 100 The mathematical expression of the crystal plane spacing changing with SOC state is obtained by fitting the polynomial function in Table 1.

[0045] Table 1 Relationship between interplanar spacing and SOC

[0046]

[0047] The electrochemically active specific surface area of ​​graphite particles at different SOC states can be calculated by the following equation: (lithiation removal is a reversible process of lithium insertion)

[0048]

[0049]

[0050]

[0051]

[0052] Where: x represents the SOC state; A (average length) and B (average width) represent the characteristic side lengths of graphite particles (see Figure 2 ); functions f(x) and g(x) are shown in Table 1.

[0053] Since the volume of graphite will shrink or expand during the lithium deintercalation reaction, in order to accurately obtain the specific surface area of ​​graphite particles under certain working conditions, it is necessary to relate the volume change of graphite to SOC. The shrinkage or expansion of graphite particles in the A and B directions is very small and can be ignored. Therefore, A and B in Formula 1 can be considered as constant terms. 100 and d 002 The change in interplanar spacing is expressed through its relationship with SOC, and the expression is shown in Table 1.

[0054] The characteristic side lengths (A and B, such as Figure 2), and select a suitable formula according to the SOC state of the graphite pole piece, and substitute the values ​​of A and B to obtain the electrochemically active specific surface area of ​​the graphite particles under different SOC states. Then, the electrochemically active area of ​​the graphite pole piece is calculated based on the mass of graphite in the graphite pole piece.

[0055] The technical solution of the present invention has the following advantages:

[0056] 1. The method for obtaining the electrochemically active area of ​​a graphite pole piece provided by the present invention is to obtain the characteristic side length of the graphite particles in the graphite pole piece by scanning electron microscopy, and select a suitable formula according to the SOC state of the graphite pole piece, and substitute the values ​​of A and B into it to obtain the electrochemically active specific surface area of ​​the graphite particles under different SOC states. The present invention uses graphite mass and graphite crystal structure (the interplanar spacing d of the characteristic crystal plane) to obtain the electrochemically active specific surface area of ​​the graphite particles under different SOC states. 100 and d 002 ) and the characteristic dimensions of the graphite particles (characteristic side lengths A and B) are used to calculate the electrochemically active specific surface area of ​​the graphite particles participating in the electrochemical reaction of lithium insertion and extraction; the electrochemically active area of ​​the graphite pole piece is obtained according to the mass of the graphite pole piece. The electrochemically active area of ​​the graphite pole piece obtained by the method provided by the present invention is closer to the actual electrochemically active area participating in the lithium insertion and extraction reaction than the area directly using the pole piece area or the area calculated by the BET method. In addition, the present invention fully considers that the volume expansion of graphite will occur during the lithium insertion and extraction process, which will cause its cross-sectional area to change at the same time. Therefore, it is obviously inappropriate to use one area to represent the chemically active area of ​​graphite within the entire SOC (state of charge) range. The method of the present invention can characterize the electrochemically active area of ​​the graphite pole piece under different SOC states. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0058] Figure 1 It is a schematic diagram of the graphite crystal structure;

[0059] Figure 2 is a schematic diagram of the morphology of graphite particles;

[0060] Figure 3 is the XRD spectrum of graphite particles when SOC is 0% in the embodiment;

[0061] Figure 4 is a scanning electron microscope image of a graphite pole piece in an embodiment of the present invention;

[0062] Figure 5 This is a comparison chart of the electrochemical active area of ​​graphite electrodes obtained by different methods. DETAILED DESCRIPTION

[0063] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0064] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0065] Example 1

[0066] This embodiment provides a method for obtaining the electrochemical active area of ​​a graphite electrode, and the specific steps are as follows:

[0067] This method is used to calculate the lithium deintercalation area of ​​an artificial graphite electrode with a diameter of 14 mm and an active material mass of 21.5 mg.

[0068] First, a graphite particle electron microscope image is obtained by scanning electron microscopy. The characteristic sizes of the graphite particles are A=10.38 μm and B=6.18 μm. Figure 4 shown.

[0069] Then, according to the graphite d 002 and d 100 The relationship between the interplanar spacing and SOC (as shown in the following table) is used to calculate the electrochemical active area of ​​graphite particles:

[0070]

[0071] The effective specific surface area of ​​graphite particles under different SOC states can be calculated by the following equation:

[0072]

[0073]

[0074]

[0075]

[0076] The calculated electrochemical active area of ​​graphite particles is:

[0077] SOC,x 0% 5% 10% 15% 20% 25% 30% <![CDATA[Area, cm 2 > 52.90 52.95 53.60 54.36 54.66 55.24 55.19 SOC,x 35% 40% 45% 50% 55% 60% 65% <![CDATA[Area cm 2 > 55.14 55.09 55.04 54.99 54.94 54.90 54.85 SOC,x 70% 75% 80% 85% 90% 95% 100% <![CDATA[Area cm 2 > 54.80 54.75 54.70 57.16 57.16 57.16 57.16

[0078] The electrochemically active area of ​​the graphite particles is calculated based on the electrochemically active area of ​​the artificial graphite pole piece with a diameter of 14 mm and a graphite mass of 21.5 mg:

[0079] The electrochemical active area of ​​the artificial graphite electrode is calculated based on BET: 1.19 m 2 / g×21.5mg=255.85cm 2 (This method keeps the BET specific surface area constant at different SOCs);

[0080] The electrochemical active area of ​​the artificial graphite electrode is calculated according to the method provided in this embodiment: 21.5 mg×A effective ;

[0081] The area of ​​artificial graphite pole piece is used as its electrochemical active area: π(14mm / 2) 2 =1.54cm 2 (This method keeps the BET specific surface area constant at different SOCs).

[0082] Comparison of the electrochemical active area of ​​the artificial graphite electrode calculated by the electrode area, the BET method and the method provided in this embodiment. Figure 5 As shown. The effective area obtained in this embodiment is smaller than the area calculated by BET and larger than the electrode area, which is in line with expectations. And the effective area obtained using this method can change with the SOC.

[0083] The results provided by the present invention are closer to the actual theoretical analysis description:

[0084] Figure 4 The left image is a scanning electron microscope image of the graphite electrode in the embodiment of the present invention, wherein the left image is an electron microscope image of the electrode surface, and the right image is an electron microscope image of the electrode cross section. Figure 4 From the right figure, it can be concluded that the size range of graphite particles in the thickness direction is about 2-3μm. According to the values ​​of characteristic dimensions A and B, the ratio of the side area to the surface area of ​​a characteristic graphite particle is:

[0085] P=(AC+BC) / (AB+AC+BC)≈34%~43.6%;

[0086] The total area ratio of the electrochemical active area calculated by the embodiment of the present invention and the BET area calculated is about 21.5%. This value is very close to the above P value. The main reason for the inconsistency is the defects of the graphite particles, and the specific surface area of ​​the BET test is much larger than the geometric area.

[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for obtaining the electrochemical active area of ​​a graphite electrode, characterized in that: The steps include: S1, obtaining characteristic dimensions of graphite particles by scanning electron microscopy, including the average length A and average width B of graphite particles; S2, determine the interplanar spacing d between graphite particles and different SOC states 100 , d 002 The changing relationship between S3, calculate the electrochemical active specific surface area of ​​graphite particles under different SOC states according to the following formula: S4, obtaining the electrochemical active area of ​​the graphite electrode according to the mass of graphite in the graphite electrode; Wherein, step S2 comprises: S21, the XRD spectrum of the graphite electrode during the charge and discharge process is measured by in-situ XRD, and the interplanar spacing d of the graphite particles is determined according to the diffraction angles corresponding to the 100 crystal plane and the 002 crystal plane. 100 and d 002 ; S22, the interplanar spacing d between graphite particles and different SOC states were obtained by fitting multiple functions 100 and d 002 The changing relationship between In step S4, the calculation method of the electrochemical active area of ​​the graphite electrode is: S e =m a *A effective , Among them, m a is the mass of graphite in the graphite electrode.

2. The method for obtaining the electrochemical active area of ​​a graphite electrode according to claim 1, characterized in that: In step S21, the interplanar spacing is calculated according to the following formula: 2dsinθ=λ, where θ is the XRD diffraction angle, λ is the X-ray wavelength, and d is the interplanar spacing.

3. The method for obtaining the electrochemical active area of ​​a graphite electrode according to claim 1, characterized in that: The diffraction angle corresponding to the crystal plane 100 of the graphite particle is 2θ=43-45°.

4. The method for obtaining the electrochemical active area of ​​a graphite electrode according to claim 1, characterized in that: The diffraction angle corresponding to the 002 crystal plane of the graphite particle is 2θ=17-23°.

5. The method for obtaining the electrochemical active area of ​​a graphite electrode according to claim 1, characterized in that: The test parameters of the in-situ XRD are 20KV and 40A, and the wavelength of the copper target X-ray is The scanning range is 10°-80°, and the scanning rate is 2° / min.

6. The method for obtaining the electrochemical active area of ​​a graphite electrode according to any one of claims 1 to 5, characterized in that: The different SOC states and the interplanar spacing d of graphite particles 100 and d 002 The changing relationship between them is:

7. The method for obtaining the electrochemical active area of ​​a graphite electrode according to claim 6, characterized in that: The electrochemical active area of ​​graphite particles under different SOC states is calculated according to the following formula:

Citation Information

Patent Citations

  • High ratio surface squama graphite for the electrochemical capacitor of the electrode material

    CN101009161A

  • Nano graphene platelet-based composite anode compositions for lithium ion batteries

    CN101849302A